The status of crop-livestock systems and evolution towards integration - Iiyama, Miyuki; Kaitibie, S.; Kariuki, P.; Morimoto, Y. (2007)
This article presents the current state of crop-livestock systems in developing countries, and reviews the recent literature on “ crop-livestock integration” as an alternative land use option for agro-pastoralists to cope with the changing environment in sub-saharan Africa and other developing regions. Mixed crop-livestock systems are one of the dominant agricultural systems in the developing world. While crop-livestock systems tremendously vary across different biophysical and demographic settings, agro-pastoralists face challenges such as population growth and globalisation. Changes in the lifestyles of agro-pastoralists and market access tend to lead to commercialised farming, while population pressures lead to scarcities and degradation of resources for conventional extensive farming. Crop-livestock integration is viewed as an economically feasible and environmentally sound solution for poor agro-pastoralists to achieve sustainable agricultural production. Optimal pathways for crop-livestock integration should achieve the best utilisation of locally available resources without much reliance on external inputs through recycling of crop/animal residuals. Although such pathways may be determined by use of systems analysis, it is recognised that the realities of the system are often more complicated than the predicted optimal pathways suggest, due to diversities in agro-ecological, demographic, and market conditions as well as to socio-economic factors. Hence, this review investigates the determinants of crop-livestock intensification and summarizes inferences for future research challenges. It draws the conclusion that crop-livestock integration should be analysed from a holistic/integrated perspective.